Behavior when socially anxious individuals expect to be (dis)liked: The role of self-disclosure and mimicry in actual likeability. (December 2020) - Voncken, Marisol J.; Dijk, Corine; Lange, Wolf-Gero; Boots, Lizzy M.M.; Roelofs, Jeffrey
Abstract: Background and objectives: This study aimed to unravel the relationship between socially anxious individuals' expectation of being (dis)liked and actual likeability by looking at the mediating role of both strategic and automatic social behavior: Self-disclosure as well as mimicry were examined. Method: Female participants (N = 91) with various levels of social anxiety participated in a social task with a confederate. Before the task, participants indicated their expectation of being liked by the confederate. Afterwards, objective video-observers rated the likeability of the participants before and after the social task as well as their level of self-disclosure and mimicry. Results: Social anxiety correlated negatively with the expectation to be liked but was not related to observer ratings of likeability, self-disclosure or mimicry. However, degree of social anxiety moderated the relation between expectations and self-disclosure. As expected, participants with low levels of social anxiety disclosed more if they expected to be liked. A reversed pattern was found for the high socially anxious participants: Here, higher expectations of being liked were related to less self-disclosure. Limitations: The study used an analogue female sample. Our social interaction task was highly structured and does not reflect informal day-to-day conversations. Conclusion: Socially anxious individuals function rather well in highly structured social tasks. No support was found for declined likeability or disrupted mimicry. Nevertheless, high socially anxious individuals did have a cognitive bias and show a self-protective strategy: when expecting a neutral judgment they reduce their level of self-disclosure. This pattern probably adds to their feelings of social disconnectedness. Highlights: In high structured social tasks socially anxious individuals function well. No relation between social anxiety and both likeability and mimicry was found. Social anxiety was related to a reduced expectation of being liked. Socially anxious participants showed reduced self-disclosure when expecting to be liked. Hence, social anxiety was marked with a cognitive bias and self-protective strategy.